THE TRANSFORMATION OF INDONESIAN EDUCATION POLICY: CURRICULUM INNOVATION, EQUAL ACCESS, DIGITALISATION, AND POLICY IMPLEMENTATION CHALLENGES (LITERATURE REVIEW) - Abdul Wahab Syakhrani (Adisam Publisher, 2025)
This study examines the transformation of education policy in Indonesia, focusing on curriculum innovation, equal access, digitisation of education, and policy implementation challenges. Through a systematic literature review approach, this study analyses various literature, policy documents, and scientific sources related to the development of education policy from time to time to the current digital era. The results of the study show that curriculum innovations such as the Merdeka Curriculum play an important role in increasing the flexibility and quality of 21st-century learning, while efforts to equalise access to education still face geographical and socio-economic constraints. The digitisation of education has become a catalyst for transformation, but faces challenges in terms of infrastructure and digital literacy that need to be addressed comprehensively. The findings of the study emphasise the importance of comprehensive synergy between stakeholders and data-based policies to realise an inclusive, adaptive, and equitable national education system. This study contributes to the development of education policies that are responsive to social and technological changes in Indonesia.